2010
DOI: 10.1016/j.otsr.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Common peroneal nerve palsy complicating knee dislocation and bicruciate ligaments tears

Abstract: Level IV, prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 29 publications
2
56
1
8
Order By: Relevance
“…This compares favorably to the previously reported nerve recovery rates (31%-75%) [2,11,23,24,27]. The variability of the existing literature likely results from injury heterogeneity and the definition of ''recovery.''…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This compares favorably to the previously reported nerve recovery rates (31%-75%) [2,11,23,24,27]. The variability of the existing literature likely results from injury heterogeneity and the definition of ''recovery.''…”
Section: Discussionsupporting
confidence: 79%
“…The peroneal nerve is at risk because it is held tightly against the fibular head [11] and injury often is associated with proximal fibular fractures and posterolateral corner injuries [5,17]. Recovery of nerve injury is variable, reported as ranging from 31% to 75% [2,11,23,24,27]. However, morbidity associated with persistent nerve dysfunction and foot drop is considerable [3].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, they found that the anatomic status of the CPN, subjected to violent traction by dislocation, was the most significant prognostic factor for neurologic recovery. In about 25% of dislocations, contusion-elongation over several centimeters was associated with as poor a prognosis as total rupture [5]. In our case, the CPN was functioning appropriately.…”
Section: /6mentioning
confidence: 46%
“…Recent studies show that the occurrence rate of CPN palsy associated with knee dislocation or bicruciate ligament injury ranges from 10% to 40%. [3][4][5] Palsy of the CPN was associated with dislocation of the knee in 25% of patients as reported by Niall et al, 16 exclusively with dislocations involving a disruption of the PCL and posterolateral corner. It is important to note that in dislocations with disruption of the PCL and posterolateral corner, the incidence is greater and may be as high as 45%.…”
Section: Discussionmentioning
confidence: 99%